Impact of bedaquiline on treatment outcomes of multidrug-resistant tuberculosis in a high-burden country. Issue 6 (10th June 2021) - Chesov, Dumitru; Heyckendorf, Jan; Alexandru, Sofia; Donica, Ana; Chesov, Elena; Reimann, Maja; Crudu, Valeriu; Botnaru, Victor; Lange, Christoph
Background: Evaluation of novel anti-tuberculosis (TB) drugs for the treatment of multidrug-resistant (MDR)-TB continues to be of high interest on the TB research agenda. We assessed treatment outcomes in patients with pulmonary MDR-TB who received bedaquiline-containing treatment regimens in the Republic of Moldova, a high-burden MDR-TB country. Method: We systematically analysed the SIMETB national electronic TB database and performed a retrospective propensity score-matched comparison of treatment outcomes in a cohort of patients with MDR-TB who started treatment during 2016–2018 with a bedaquiline-containing regimen (bedaquiline cohort) and a cohort of patients treated without bedaquiline (non-bedaquiline cohort). Results: Following propensity score matching, 114 patients were assigned to each cohort of MDR-TB patients. Patients in the bedaquiline cohort had a higher 6-month sputum culture conversion rate than those in the non-bedaquiline cohort (66.7% versus 40.3%; p<0.001). Patients under bedaquiline-containing regimens had a higher cure rate assessed by both World Health Organization (WHO) and TBnet definitions (55.3% versus 24.6%; p=0.001 and 43.5% versus 19.6%; p=0.004, respectively), as well as a lower mortality rate (8.8% versus 20.2%; p<0.001 and 10.9% versus 25.2%; p=0.01, respectively). In patients who previously failed on MDR-TB treatment, >40% of patients achieved a cure with a bedaquiline-containing regimen. Conclusions: Bedaquiline-based MDR-TB treatment regimens result in better disease resolution when compared with bedaquiline-sparing MDR-TB treatment regimens under programmatic conditions in a country with a high burden of MDR-TB. Used under programmatic conditions in a high-burden MDR-TB setting, bedaquiline-based MDR-TB treatment regimens result in faster and more sustained disease resolution than bedaquiline-sparing MDR-TB treatment regimens https://bit.ly/37mSQOT